2013
DOI: 10.1371/journal.pone.0059210
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleocapsid Protein of Rift Valley Fever Virus Is a Potent Human CD8+ T Cell Antigen and Elicits Memory Responses

Abstract: There is no licensed human vaccine currently available for Rift Valley Fever Virus (RVFV), a Category A high priority pathogen and a serious zoonotic threat. While neutralizing antibodies targeting the viral glycoproteins are protective, they appear late in the course of infection, and may not be induced in time to prevent a natural or bioterrorism-induced outbreak. Here we examined the immunogenicity of RVFV nucleocapsid (N) protein as a CD8+ T cell antigen with the potential for inducing rapid protection aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…Influenza virus conserved internal nucleoprotein promotes heterosubtypic immunity due to antibodies against the NP involving CD8+T cells in an antibody dependent manner [48] and mice immunized with an ubiquitinated form of the RVFV nucleoprotein displayed higher levels of anti-N antibodies and antigen-specific T-cell responses [49]. Recent data confirmed the RVFV nucleoprotein as a potent human CD8+ T cell antigen [50].…”
Section: Discussionmentioning
confidence: 92%
“…Influenza virus conserved internal nucleoprotein promotes heterosubtypic immunity due to antibodies against the NP involving CD8+T cells in an antibody dependent manner [48] and mice immunized with an ubiquitinated form of the RVFV nucleoprotein displayed higher levels of anti-N antibodies and antigen-specific T-cell responses [49]. Recent data confirmed the RVFV nucleoprotein as a potent human CD8+ T cell antigen [50].…”
Section: Discussionmentioning
confidence: 92%
“…The World Organization for Animal Health (OIE) specified the RVFV as a high consequence pathogen , while the United States Department of Agriculture, Animal and Plant Health Inspection Service (USDA, APHIS) designated the RVFV as the third most dangerous animal threat Namibia from 2009 to 2011 (Métras et al, 2012;Monaco et al, 2013), Mauritania in 2010 and Mauritania and Senegal from 2012 to 2015 (Sow et al, 2014(Sow et al, , 2016, and also Niger and Uganda in 2016 with 1220 confirmed human deaths and > 0.5 million estimated human cases (Dar et al, 2013;Hartman, 2017). However, due to the higher fatality rates, RVFV could be a greater threat to the public health, especially in non-endemic regions (Xu et al, 2013). To date, no licensed vaccine or approved therapeutics is available.…”
Section: Introductionmentioning
confidence: 99%
“…For initial studies, PBMC from two healthy donors were used to generate monocyte-derived dendritic cells, as described [40]. Dendritic cells from each donor were transduced with a lentiviral vector expressing full length MAM-A and co-cultured at a dendritic cell to T cell ratio of 1:10 with autologous CD8 T cells (2 × 10 6 /mL) purified by magnetic bead separation (Miltenyi Biotec; Auburn, CA).…”
Section: Methodsmentioning
confidence: 99%
“…With this unbiased approach, MAM-A-derived epitopes are naturally processed, presented, and recognized by functional T cell repertoires. The same techniques have been used successfully to identify novel RVFV epitopes [40]. We identified three novel HLA-A2-restricted MAM-A epitopes.…”
Section: Introductionmentioning
confidence: 99%